Design and modal analysis of flat plate with eccentric hole - Nuraini, Aziz (2012)
This project presents on an experimental study of flat plates with eccentric hole that always can be found in the nuclear reactor or other mechanical components. The flat plates with an eccentric hole was prepared and dynamic properties will be investigated using experimental modal analysis and validation by finite element analysis (FEA). The modal testing experiment will be done in the lab scale and data acquisition system (DAQ) will be used to interpret data collected from modal into the computer and generate frequency response function (FRF). This FRF consists natural frequency, damping coefficient and mode to determine dynamic characteristics of the flat plates with eccentric hole. It was observed that, from both result, an eccentric hole on flat plates affected the dynamic properties compare to flat plate without hole. This experimental and finite element analysis produced five different mode and natural frequencies that contributed to the prediction dynamic properties of the flat plate with eccentric hole. This result offers significant values on structure or component analysis of the nuclear reactor component and mechanical components.